Introduction, issue 76 - Mabro, R (Oxford Institute for Energy Studies, 2009)
Six articles published here are grouped under two different headings: the EU Energy Policy and Features of Recent Oil Developments. Both are highly topical. The financial crisis which risks to push the environmental objective toward the back burner, the election of President Obama which on the contrary involves a greater concern with that objective, and the Russian–Ukrainian gas supply crisis, all call for an appraisal of the EU ambitious energy policy. The current state of the world petroleum market characterised by relatively low prices, falling oil demand, a reluctance to invest, distorted futures prices, and considerable uncertainties also calls for an analysis of some of its aspects.